Pengaruh Sertifikasi Sistem Manajemen ISO-9001:2015 Terhadap Pertumbuhan Kinerja PT Semen Indonesia Logistik - Bintang Karahianan; Raden Johnny Hadi Raharjo (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study aims to analyze the effectiveness of ISO 9001:2015 implementation through the Process Approach, PDCA, and Risk-Based Thinking and their contribution to improving the performance of PT Semen Indonesia Logistik. The method used was descriptive qualitative through interviews, observations, and documentation studies. The results indicate that most units, particularly systems management and human capital, are in the very effective category with scores of 4 to 5, while operations and marketing are in the effective category with scores of 3.2 to 3.8. The PDCA cycle has been proven to operate consistently, although strengthening documentation and collective corrective actions are still needed. The implementation of Risk-Based Thinking is also considered mature, although data-based monitoring needs to be improved. Overall, the integration of these three approaches can improve operational stability, process reliability, and service quality, contributing to the company's upward performance trend during 2022-2023.